Spectroscopic Analysis of Organic Matters Derived from Urban Atmospheric Aerosols - Uspenski, A.A.; Stepakov, A.V. (Asian Journal of Chemistry, 2019)
The composition of organic matter derived from PM2.5 fraction of urban aerosols collected in Saint-Petersburg during the annual cycle was investigated by 1H NMR, 13C NMR and IR spectroscopies. It was found that the composition of organic fraction varies slightly with the seasons. The main organic components of aerosol extracts are aliphatic oxygen-containing compounds (such as derivatives of carboxylic acids and esters), whose content is maximum in winter samples. Aromatic compounds are present in aerosol extracts in negligible quantities. The results showed a significant contribution of the process of combustion of automotive fuel in the formation of low molecular weight organic compounds that are present in the composition of urban aerosol.